Electron Mobility in an Unintentionally Doped GaN/AlGaN Surface Quantum Well - Minh, Nguyen Viet (Communications in Physics, 2012)
We present a theoretical study the two-dimensional electron gas 2DEG at low temperature in an unintentionally doped GaN/AlGaN surface quantum well, taking adequate account of the roughness-induced scattering mechansms and effect due to sheet polarization charges.  Within model of surface quantum wells 2DEG be described by an extended Fang-Howard wave function, we are able to derive an analytic expression for the self-consistent Hartree potential. Thus, we obtained simple expresion describing the enhancement of the 2DEG screening and unscreened\break potentials for different scattering sources. We studied the electron mobility due to different scattering sources and the total electron mobility in an unintentionally doped GaN/AlGaN surface quantum well.